(untitled) (Balthazar, 2020)
Born and raised in Lebanon, Seb Alex moved to Europe in 2011 to pursue his career in Sustainable Architecture. Having worked with the UNHCR’s refugee program for a year, he then worked as an international coordinator of projects for an architecture company in Barcelona. A year after, he decided to leave his corporate life behind and dedicate all his time to animal rights advocacy. During 2018, he gave talks on Vegan Advocacy, Why Veganism, Why Activism and Learning From Previous Struggles across Europe and Australia. In 2019, he was invited to speak about Animal Exploitation & Sustainability in universities and schools. He is now helping out with the organisation of grassroots activism events and giving lectures on Speciesism & Sustainability in Europe and South Africa. During these years dedicated to activism and to dialoguing with non-vegan people, he noticed their frequent use of arguments based on logical fallacies. The constant confrontation with such arguments pushed him to develop a project that will give outreachers an effective instrument to elaborate clrarer and more constistent answers: a brief manual that will reveal the logical fallacies on which such specist arguments are based. The text, that will be distributed online as an e-book, is soon to be published.